Doing Business in Indonesia 2010 - World Bank; International Finance Corporation (Washington, DC, 2017)
Doing Business in Indonesia 2010 is the first country-specific sub national report of the doing business series in Indonesia and the third in East Asia, following the reports on China and the Philippines. It measures business regulations and their enforcement in 14 Indonesian cities: Balikpapan, Banda Aceh, Bandung, Denpasar, Jakarta, Makassar, Manado, Palangka Raya, Palembang, Pekanbaru, Semarang, Surabaya, Surakarta and Yogyakarta. The cities can be compared against each other, and with economies worldwide. This project is endorsed by the Government of Indonesia through the Ministry for Administrative Reforms (Menpan) and it is the result of cooperation between the International Finance Corporation and the Regional Autonomy Watch. The indicators analyzed in doing business in Indonesia 2010 are based on standardized case scenarios with specific assumptions, such as that the business is located in one of the 14 cities benchmarked in the report. Economic indicators commonly make limiting assumptions of this kind. Inflation statistics, for example, are often based on prices of consumer goods in a few urban areas. Such assumptions allow global coverage and enhance comparability, but they inevitably come at the expense of generality. In defining the indicators, doing business in Indonesia 2010 assumes that entrepreneurs are knowledgeable about all regulations in place and comply with them. In practice, entrepreneurs may spend considerable time finding out where to go and what documents to submit.